2010
DOI: 10.1590/s0006-87052010000400028
|View full text |Cite
|
Sign up to set email alerts
|

Temperatura do ar em sistemas de produção de café arábica em monocultivo e arborizados com seringueira e coqueiro-anão na região de Mococa, SP

Abstract: A técnica de cultivos consorciados ou arborizados de cafezais visa atenuar as adversidades meteorológicas extremas podendo contribuir para o desenvolvimento do cultivo. O trabalho teve como objetivo caracterizar a temperatura do ar em sistemas de arborização de cafeeiros, comparado com o plantio a pleno sol. Foram realizadas avaliações em experimento de campo, implantado em 1999, no município de Mococa, representativo de uma das mais importantes regiões produtoras de café do Estado de São Paulo. As mensurações… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
8
0
3
Order By: Relevance
“…In most situations, drought impacts can be greatly aggravated by supra-optimal air temperatures 15 . Extreme temperatures, depending on their intensity, duration, and speed of imposition, impair cell metabolic processes (e.g., photosynthesis) 16,17 , growth and survival of plants, as well as their economic exploitation 16 . In the region of study, it is common the occurrence of summer temperatures reaching up to 40 °C.…”
mentioning
confidence: 99%
“…In most situations, drought impacts can be greatly aggravated by supra-optimal air temperatures 15 . Extreme temperatures, depending on their intensity, duration, and speed of imposition, impair cell metabolic processes (e.g., photosynthesis) 16,17 , growth and survival of plants, as well as their economic exploitation 16 . In the region of study, it is common the occurrence of summer temperatures reaching up to 40 °C.…”
mentioning
confidence: 99%
“…In the reduction of the solar radiation flux, observed inside the agroforestry systems of the present work, there was reduction of the air heating process by irradiation, which was reflected in a decline in air temperature. Valentini et al (2010) observed that the greatest effects of the production system with the presence of the arboreal component were observed in the maximum air temperature, where a greater reduction in the values for the summer and spring seasons can be observed. Menezes et al (2002) found reductions of 2, 8°C in the maximum temperatures under canopies of Ziziphus joazeiro in relation to full sun Marin et al (2006) observed increments up to 2°C at maximum air temperature at three meters distance from Gliricidia sepium trees when compared to measurements more near to the plant.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the species of shade tree affects PAR interception (COELHO et al, 2010), evaporative rates (PADOVAN et al, 2018;PADOVAN et al, 2015), air (RICCI et al, 2013;VALENTINI et al, 2010) and soil temperature, as well as thermal amplitude (RICCI et al, 2013).…”
Section: Canopy Density and Canopyoccupation Ratementioning
confidence: 99%